Failure behavior of laminated composites under anticlastic bending - Alpay, Yakup Okan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
In this study, failure behavior of laminated composite plates subjected to anti-clastic bending is investigated. Anticlastic bending is a special case of bi-axial out-of-plane loading that applies predominantly twisting moment. A unique test fixture is designed to achieve anticlastic loading condition. Totally nine different configurations are chosen and four specimens are tested for each configuration. Reinforcing strips are bonded to the edges of the specimens to reduce the delamination risk at the edges. Acoustic emission monitoring (AEM) is utilized to detect the first-ply-failure load. In this method, sounds resulting from initiation and progression of damage within the material are detected, then the signal data are processes to identify the failure modes and determine their time of occurrence. An FE model is developed to simulate the anticlastic bending test. A code is developed using ANSYS Parametric Design Language to obtain the first ply failure predictions of maximum stress, maximum strain, Tsai-Wu, Tsai-Hill, Hashin, Hoffman and quadric surfaces failure criteria. The experimental and numerical results are then compared. Relative strengths and weaknesses of the failure criteria in estimating failure of laminated composite plates under anticlastic bending are determined.
Keywords: Composite materials.